The Relationship Between Autophagy and Brain Plasticity in Neurological Diseases - Wang, Man-Man; Feng, Ya-Shuo; Yang, Si-Dong; Xing, Ying; Zhang, Jing; Dong, Fang; Zhang, Feng (Frontiers in Cellular Neuroscience, 2019)
Autophagy, a catabolic degradation system, is utilized for destroying and recycling the damaged or unnecessary cellular components. Brain plasticity refers to the remarkable characteristics of brain neurons that change their structure and function according to previous experience. This review was performed by searching the relevant articles in databases of SCIENCEDIRECT, PUBMED, and Web of Science, from respective inception to January 2019. Here, we review the neuroprotective effect of autophagy in neurological diseases and the mechanism of autophagy in brain plasticity. Moreover, the mechanism of autophagy in the process of brain plasticity can provide the possibility for the development of new treatment methods in the future, thus benefiting patients with neurological diseases. In summary, autophagy and brain plasticity play important roles in neurological diseases.